อิทธิพลของผู้แนะนำสินค้าที่เป็นผู้มีชื่อเสียงด้านกีฬาที่มีผลต่อความตั้งใจซื้อสินค้าของผู้บริโภค - ชนิดา จุลรัตนมณี (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research was conduct to compare the intention to purchase of consumers between Sports Brands and Non-Sports Brands products that were promoted by Athlete Endorsers and Stars Endorsers. This research also compare products’ purchase intention between sport interested and sport disinterested consumers in different type of endorser. The samples were people that interested and disinterested in sport, separated to 200 subjects in each group, total of 400 subjects from judgement sampling would answered the questionaire which was used as a survey tool. The collected data were statistically analyzed in terms of frequencies, percentages, means, standard deviations and t-test. Results 1. Celebrity Athlete Endorser and Celebrity Endorser were effective to purchase intention of sport disinterested in both of Sport Brands and Non-Sport Brands products, found significantly difference at .05 level. 2. Celebrity Athlete Endorsers and Celebrity Endorsers were not effective to purchase intention in Sport Brands products, but were effective to Non-Sport Brands products in Sport interested consumers. 3. Sport interested and Sport disinterested consumers have purchase intention in Sport Brands products that were promoted by Athlete Endorsers, found not to be significantly difference. 4. Sport interested and Sport disinterested consumers have purchase intention in Non-Sport Brands products that were promoted by Celebrity Endorsers, found not to be significantly difference.